Late Pleistocene to Recent Deformation in the Thick‐Skinned Fold‐and‐Thrust Belt of Northwestern Argentina (Central Calchaquí Valley, 26°S). Issue 1 (29th December 2020) - Figueroa, Sara; Weiss, Jonathan R.; Hongn, Fernando; Pingel, Heiko; Escalante, Leonardo; Elías, Leonardo; Aranda‐Viana, R. Germán; Strecker, Manfred R.
Abstract: The thick‐skinned fold‐and‐thrust belt on the eastern flank of the Andean Plateau in northwestern Argentina (NWA) is a zone of active contractional deformation characterized by fault‐bounded mountain ranges with no systematic spatiotemporal pattern of tectonic activity. In contrast, the thin‐skinned Subandean fold‐and‐thrust belt of northern Argentina and southern Bolivia is characterized primarily by in‐sequence (i.e., west to east) fault progression, with a narrow zone of Quaternary deformation focused at the front of the orogenic wedge. To better understand how recent deformation is accommodated across these mountain ranges and the Argentinian portion of the orogen in particular, estimating and comparing deformation rates and patterns across different timescales is essential. We present Late Pleistocene shortening rates for the central Calchaquí intermontane valley in NWA associated with at least three episodes of deformation. Global Positioning System data for the same region reveal a gradual decrease in horizontal surface velocities from the Eastern Cordillera toward the foreland, which contrasts with the rapid velocity gradient associated with a locked décollement in the Subandean Ranges of southern Bolivia. Our new results represent a small view of regional deformation that, when considered in combination with the shallow crustal seismicity and decadal‐scale surface velocities, support the notion that strain release in NWA is associated with numerous slowly deforming structures that are distributed throughout the orogen. Key Points: Analysis of deformation in northwestern Argentina reveals that numerous, widely distributed, localized structures accommodate shortening No well‐defined deformation front or clear indication of a locked décollement underlying the region exists This behavior is fundamentally different from the thin‐skinned fold‐and‐thrust belt of southern Bolivia and northernmost Argentina